Experiences in the treatment of patients with multiple head and neck paragangliomas - Künzel, Julian; De Tristan, Julie; Mantsopoulos, Konstantinos; Koch, Michael; Baussmerth, Marcela; Zenk, Johannes; Iro, Heinrich (American Journal of Otolaryngology, 2014)
To analyze treatment results in the multidisciplinary management of patients with multiple head and neck paragangliomas (HNPs).Retrospective analysis including all patients with multiple HNPs (VP, vagal paraganglioma; JTP, jugulotympanic paraganglioma; CBT, carotid body tumor) treated between 2000 and 2013 at a tertiary referral center.Ten patients (three men, seven women) had 25 HNPs (two VPs, eight JTPs, and 15 CBTs). The age range at diagnosis was 31-71 years (mean 40.9 years, median 37 years). Nine tumors (four CBTs, three JTPs, two VPs) were treated only with stereotactic radiotherapy (SRT; 50.4-56Gy, mean 55.3Gy) or in one case intensity-modulated radiotherapy (60 Gy). Nine tumors were treated with surgery alone (eight CBTs, one JTP) and three JTPs with subtotal surgery combined with adjuvant SRT. A "wait and scan" strategy was used in three cases (two CBTs, one JTP). The mean follow-up period was 4.3 years (range 0.1-13 years, median 4 years). The rate of tumor control with surgery and/or SRT was 100% (21/21). One patient with a wait-and-scan strategy for CBT had slow asymptomatic progression during a 13-year follow-up.The treatment results in this series of patients with multiple HNPs show that a very high rate of long-term tumor control with low morbidity can be achieved using tailored and individualized approaches. All of the different treatment strategies available should be discussed with the patient. In particular, the treatment should involve a multidisciplinary team of experts in the fields of nuclear medicine, genetics, pathology, radiology, radio-oncology, and surgery.
EVALuna2:18180